Telecommunication Accessibility and Local Economic Dynamics in Indonesia’s 3T Regions - Yoze Rizal; Agus Arnold Nalle; Yeheskial Adrian Roen; I Putu Yoga Bumi Pradana (Catalist Indo Publisher, 2026)
Background Telecommunication accessibility is a key driver of inclusive development, particularly in Indonesia’s 3T (Disadvantaged, Frontier, and Outermost) regions, where geographical isolation and infrastructure limitations constrain economic opportunities. To reduce the digital divide, the Indonesian government has prioritized national programs such as the Palapa Ring and the deployment of Base Transceiver Stations (BTSs). This study examines how these initiatives influence telecommunication accessibility and local economic dynamics in East Nusa Tenggara (NTT). Methods This study employed a qualitative case study approach. Data were collected through in-depth interviews with local government officials, telecommunication providers, community leaders, and end users, complemented by field observations and document analysis. The data were analyzed thematically to identify access conditions, structural challenges, and local economic responses to telecommunication development. Results The findings indicate that expanding fiber-optic networks and BTS infrastructure has improved basic connectivity and reduced isolation in several 3T areas. Improved access supports micro, small, and medium enterprise activities, enhances access to digital education, and enables emerging digital-based livelihoods. However, benefits remain uneven due to persistent last-mile connectivity gaps, unstable network quality, low digital literacy, and limited affordability. Conclusions Telecommunication infrastructure development in 3T regions is necessary but insufficient for inclusive local economic growth. Integrating infrastructure expansion with digital literacy programs, affordability support, and targeted last-mile interventions is essential to maximize socio-economic benefits.